The poetics of distraction. Issue 1 (2nd January 2019) - Coles, Katharine
ABSTRACT: This lyric essay champions the value of distraction, especially in the context of creative work, in an age obsessed with focus and attention. Using personal anecdotes and close reading, the piece examines both the hazards and the benefits of allowing our attention to be diverted, especially by our inner lives.